Hypercalcemia in Lung Cancer due to Simultaneously Elevated PTHrP and Ectopic Calcitriol Production: First Case Report. (2nd July 2017) - Nemr, Saed; Alluri, Sunitha; Sundaramurthy, Dhivya; Landry, Daniel; Braden, Gregory
Abstract : Calcitriol-mediated hypercalcemia has been reported in malignant lymphomas and granulomatous diseases but not in lung carcinoma. We describe a patient with squamous cell lung carcinoma with hypercalcemia and elevated calcitriol levels. A 60-year-old Caucasian male patient with stage IIIB squamous cell lung cancer developed hypercalcemia at 14.8 mg/dL two years after receiving chemotherapy and radiotherapy where labs showed a serum intact PTH: 7 pg/mL, PTHrP: 30 pmol/L, 1, 25-hydroxyvitamin D (calcitriol): 76 pg/mL, and 25-hydroxyvitamin D levels: <4 ng/mL. Calcitriol levels were elevated despite undetectable 25-hydroxyvitamin D levels. There are no reported lung cancer cases with elevated calcitriol as an etiology of hypercalcemia. We believe that the elevated calcitriol levels in this case were due to a PTHrP-independent mechanism, possibly from either ectopic production of calcitriol in tumor cells or from increased activity of 1-alpha hydroxylase in the same cells. The patient died before the effects of prednisone therapy could be assessed. Studies are needed to investigate the cellular source of calcitriol and its role in hypercalcemia in patients with lung cancer.